Monozygotic twins with trisomy 18 of paternal origin: prenatal diagnosis and molecular cytogenetic characterization in a pregnancy with one structurally abnormal living fetus and one intrauterine fetal demise - Chih-Ping Chen; Schu-Rern Chern; Yi-Yung Chen; Pei-Chen Wu; Dai-Dyi Town; Wen-Lin Chen; Wayseen Wang (Elsevier, 2012)
Objective: To present prenatal diagnosis and molecular cytogenetic characterization of trisomy 18 in a monozygotic twin pregnancy, with one structurally abnormal living fetus and one intrauterine fetal demise. Case Report: A 38-year-old woman was referred for amniocentesis at 16 weeks of gestation because of advanced maternal age. Prenatal ultrasound revealed a monozygotic twin pregnancy, with one structurally abnormal living fetus, and one fetal demise. The body structure details of the dead fetus could not be identified, whereas holoprosencephaly and omphalocele were identified in the living fetus on prenatal ultrasound. Quantitative fluorescent polymerase chain reaction assays using polymorphic DNA markers specific for chromosome 21 and chromosome 18, were applied to the uncultured amniocytes in the amniotic cavity of the living fetus and the cultured amniocytes in the amniotic cavity of the fetus with intrauterine fetal demise. The specimen showed a dosage ratio of 2:1 (paternal:maternal) for chromosome 18-specific markers in both twins. The result was consistent with monozygosity and trisomy 18, and the trisomy 18 was possibly caused by a paternal second meiotic division non-disjunction error or a postzygotic mitotic error. Conventional cytogenetic analysis revealed a karyotype of 47,XY,+18 in both twins. The pregnancy was terminated at 19 weeks of gestation, and a 2 g small-for-date macerated twin A and a 166 g malformed twin B were delivered. Twin A manifested cebocephaly and omphalocele, and twin B manifested premaxillary agenesis and omphalocele. Conclusion: The present case provides evidence that fetal wastage may occur in one of the co-twins in monozygotic twins associated with trisomy 18, and this may in part explain the very rare occurrence of living monozygotic twins with trisomy 18.